Mitigating DDoS Attacks in Blockchain Environments Using a Multi-level Security Framework - Khara, Satvik V.; Tivari, Gaurav D. (Mathematics and Computer Science: Research Updates Vol. 5, 2025)
In the current era of rapid digital transformation, blockchain technology has emerged as one of the most disruptive innovations across multiple sectors. Apart from its growing prominence, there remains a significant lack of awareness regarding its practical applications and potential benefits. This paper briefly explores the vast applications of blockchain technology with a particular focus on the challenges encountered within the IT industry. It delves into the technical and operational hurdles that organisations face when attempting to adopt and implement blockchain solutions. By combining strategic planning, architectural best practices and risk mitigation techniques, our framework aims to facilitate more secure, scalable and cost-effective incorporation of blockchain into existing IT ecosystems. The paper proposes a comprehensive framework aimed at addressing these challenges, offering strategic insights for more effective and secure integration of blockchain into existing IT infrastructures.